Elements in landscape areas, distances, dimensions - Zimmermann, Astrid (Birkhäuser, 2020)
Designing the outdoor environment is a complex process. Landscape architects must take into account various factors such as space, distance and movement. This volume is a practical reference work for students as well as professionals. It provides all the key dimensions for vertical planning, vegetation and public spaces - everything one needs to design functional and use-specific landscapes.